Thermally conductive phase change materials and their applications
A thermally conductive phase change material using a polyfunctionally modified polysiloxane with polyether and antioxidant properties addresses compatibility and oxidation issues, maintaining thermal conductivity and phase transition, and is suitable for screen printing, enhancing heat dissipation in electronic components.
Patent Information
- Application Number
- JP2023559027
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-25
- Filing Date
- 2022-03-21
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2042-03-21
AI Technical Summary
Existing thermally conductive phase change materials suffer from issues such as poor component compatibility, susceptibility to oxidation, phase separation under thermal shocks, flammability, and incompatibility with screen printing processes, leading to increased thermal resistance and material leakage.
A thermally conductive phase change composition comprising a polyfunctionally modified polysiloxane as a base polymer, combined with thermally conductive fillers, which includes polyether functional groups and antioxidant properties, ensuring good component compatibility, oxidation resistance, and suitability for screen printing.
The composition maintains thermal conductivity and phase transition behavior under aging and thermal shock, is non-flammable, and can be easily stored, with no component precipitation, making it suitable for screen printing applications.
Smart Images

Figure 0007602666000009 
Figure 0007602666000010 
Figure 0007602666000011
Abstract
Description
[Technical field]
[0001] The present invention belongs to the field of polymeric materials, and in particular to thermally conductive phase change materials and their applications. [Background technology]
[0002] With the development of science and technology, the integration of electronic components is becoming higher and higher, and the amount of heat generated per unit volume is becoming larger and larger. The problem of heat dissipation has long been a bottleneck in design. If the heat dissipation problem is not solved, it will directly shorten the life of electronic devices and affect their normal use. In order to solve the heat dissipation problem of heat-generating electronic components, heat dissipation sheets are usually designed. However, the surfaces of electronic components and heat dissipation sheets are not completely flat, and there are more than 90% voids on the contact surface, which greatly increases the thermal resistance.
[0003] In order to reduce the thermal resistance of the interface, various solutions have been proposed in the prior art, such as the use of metal welding, thermally conductive adhesives, thermally conductive gaskets, thermally conductive silicone grease, thermally conductive phase change materials, etc. Among them, the solution using thermally conductive phase change materials has attracted attention due to its advantages such as low thermal resistance, easy disassembly and assembly, and resistance to drying.
[0004] Thermally conductive phase change materials are a kind of thermally conductive materials with phase transition ability, and can exhibit phase transition behavior in a certain temperature range. They usually become liquid at the operating temperature of electronic components (usually above 30°C), reducing the thermal resistance. They remain solid at non-operating temperatures, effectively preventing leakage.
[0005] China Patent No. 102634212 discloses a thermally conductive silicone grease composition mainly composed of carbon nanotubes, graphene, phase transition capsule particles and silicone oil. The thermally conductive silicone grease composition has high thermal conductivity and low thermal resistance, greatly improving the heat dissipation efficiency and life of the thermally conductive silicone grease, and has high practical value. However, this invention only relates to mechanically mixing capsules with phase transition ability and silicone oil, which are poorly compatible and prone to local aggregation. In addition, the composition as a whole does not show phase transition behavior, and silicone oil is prone to flow out when it is repeatedly cooled and heated.
[0006] China Patent Publication No. 109844030 relates to a thermally conductive silicone composition comprising (A) an organopolysiloxane as a base polymer and (B) a thermally conductive filler, in which the thermally conductive silicone composition contains 60-85% by volume of the thermally conductive filler, and 40-60% by volume of the thermally conductive filler is aluminum nitride having an average particle size of 50 μm or more. Summary of the Invention [Problem to be solved by the invention]
[0007] However, prior art thermally conductive phase change materials suffer from one or more of the following problems, among others: (i) If the compatibility between the components is poor, the dispersion will be non-uniform, which will tend to increase localized thermal resistance. (ii) Phase change materials are easily oxidized at high temperatures, and therefore are prone to hardening or drying, and in some cases may lose their phase transition function. (iii) Repeated cold and hot shocks are likely to cause phase separation, which may lead to leakage of components and increased thermal resistance. (iv) The material is flammable and difficult to store. (v) It is not suitable for processing by screen printing. Screen printing has strict requirements for the material to be coated, including: 1) the material to be coated must ensure good fluidity during processing; 2) the particle size of the filler contained in the material to be coated must be much smaller than the pore size of the screen; 3) no cross-linking due to chemical reaction or crystallization of certain components should occur during screen printing. Therefore, thermally conductive phase change materials that can be coated by screen printing technology are rare on the market.
[0008] The present invention aims to overcome the problems of the prior art.
[0009] Therefore, the object of the present invention is to provide a thermally conductive phase change material with excellent overall performance. In particular, the thermally conductive phase change material according to the present invention has good component compatibility. The thermally conductive phase change material according to the present invention also has good oxidation resistance. The thermally conductive phase change material according to the present invention can maintain good thermal conductivity and phase transition behavior even after aging experiments and / or long-term thermal shock; no components are precipitated even after long-term thermal shock. The thermally conductive phase change material according to the present invention is non-flammable and easy to store. The thermally conductive phase change material according to the present invention is particularly suitable for processing by screen printing. [Means for solving the problem]
[0010] Therefore, according to one aspect of the present invention, there is provided a thermally conductive phase change composition comprising a multifunctionally modified polysiloxane as a base polymer and a thermally conductive filler.
[0011] Preferably, the thermally conductive phase change composition comprises a multifunctional modified polysiloxane as a base polymer and a thermally conductive filler.
[0012] According to one embodiment, the multifunctionally modified polysiloxane as the base polymer is a difunctionally modified polysiloxane, preferably a polysiloxane modified by a polyether functional group and a functional group having antioxidant properties.
[0013] The main chain of polysiloxane is generally substantially composed of repeating units of organosiloxane. Examples of organic groups bonded to silicon atoms in organopolysiloxane include methyl, ethyl, propyl, 3,3,3-trifluoropropyl, xylyl, tolyl, and phenyl groups.
[0014] According to a preferred embodiment, the polysiloxane is a linear polydiorganosiloxane, particularly preferably a linear polydimethylsiloxane. According to another preferred embodiment, the polysiloxane is a polymethylhydrosiloxane, preferably a linear polymethylhydrosiloxane.
[0015] According to one embodiment, the polyether functional group is selected from polyalkylene oxide functional groups, preferably polyethylene oxide functional groups, polypropylene oxide functional groups, and combinations thereof, said functional groups being optionally substituted, for example by alkyl, such as methyl, ethyl, propyl, butyl, or alkenyl, such as vinyl, allyl.
[0016] According to a particularly preferred embodiment, the polyether functional group is an allyl polyoxyethylene ether functional group.
[0017] According to one embodiment, the functional groups having antioxidant properties are selected from hindered phenol functional groups, hindered amine functional groups, or combinations thereof.
[0018] The hindered phenol according to the present invention can be selected from the following: methyl β-(3,5-di-tert-butylhydroxyphenyl)propionate, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], n-octadecyl β-(4-hydroxyphenyl-3,5-di-tert-butyl)propionate, N,N'-1,6-hexylene-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], amide], N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, octadecyl 3-(3,5-di-tert-butyl-4-hydroxy)propionate, 2,6-di-tert-butyl-4-cresol, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,6-di-tert-butyl-4-methylphenol, 4,4'-methylenebis(2,6-di-tert-butylphenol), and combinations thereof.
[0019] According to a particularly preferred embodiment, the hindered phenol of the present invention is methyl β-(3,5-di-tert-butylhydroxyphenyl)propionate.
[0020] The hindered amine according to the present invention may be selected from diphenylamine, p-phenylenediamine, dihydroquinoline, and combinations thereof.
[0021] The functional groups having antioxidant properties may be located on the side chains and / or at both ends of the base polymer.
[0022] According to a particularly preferred embodiment, the polyfunctionally modified polysiloxane has the following structure: [ka] In the formula, n1 is an arbitrary integer from 10 to 100, preferably from 12 to 60, more preferably from 15 to 50, and most preferably from 18 to 42. n2 is an arbitrary integer from 6 to 120, preferably from 6 to 100, more preferably from 8 to 90, and most preferably from 10 to 80.
[0023] The phase transition temperature of the base polymer can be adjusted by changing n1. The larger the value of n1, the higher the phase transition temperature. For example, the phase transition temperature of the polyfunctional modified polysiloxane is 0°C to 80°C, preferably 20°C to 50°C.
[0024] The viscosity of the base polymer can be adjusted by changing n2. The larger the value of n2, the higher the viscosity. Preferably, the polyfunctional modified polysiloxane has a viscosity of 10 to 2000 mPa·s, preferably 200 to 1500 mPa·s, when measured at 50°C using a rotational viscometer according to the national standard GB / T10247-2008 viscosity measurement method standard.
[0025] The thermally conductive filler may be selected from the following: aluminum hydroxide, alumina, zinc oxide, cerium oxide, aluminum nitride, boron nitride, silicon nitride, silicon carbide, graphene, carbon nanotubes, quartz powder, aluminum powder, copper powder, silver powder, and mixtures thereof.
[0026] According to one embodiment, the particle size (D 50 ) is 0.1 to 50 μm, preferably 1 to 20 μm, when measured using a laser particle size analyzer commonly used in the art (such as OMEC's PIP9.1 particle image processor or Shandong Niket Analytical Instrument Co., Ltd.'s NKT2010-L dry particle size analyzer).
[0027] According to another embodiment, the thermally conductive filler may be used in combination with coarse and fine particle sizes, where the median particle size (D 50 ) can range from 5 to 20 μm, and the finer fraction median particle size (D 50) may be in the range of 0.1 to 5 μm, and the ratio of coarse to fine may be in the range of, for example, 3:7 to 7:3, preferably 4:6 to 6:4.
[0028] The thermally conductive filler preferably has a spherical or nearly spherical shape.
[0029] According to a preferred embodiment, the thermally conductive filler is surface treated with a treating agent, which is preferably selected from stearic acid, zinc stearate, calcium stearate, KH550, KH560, KH792, KH602, KH570, Dynasilan® 1146, hexamethyldisilazane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, vinyltrimethoxysilane, and mixtures thereof.
[0030] Optionally, the composition according to the invention may contain additives that may be commonly used in thermally conductive phase change compositions, provided that they do not impair the objectives of the invention. For example, the additives may be selected from pigments of different colors, reinforcing fillers such as carbon black or silica.
[0031] According to one embodiment of the present invention, the thermally conductive phase change composition comprises 5-30 wt %, preferably 8-20 wt % of the multifunctional modified polysiloxane based on the total weight of the composition.
[0032] According to one embodiment of the present invention, the thermally conductive phase change composition comprises 70-95 wt %, preferably 80-92 wt %, of the multifunctional modified thermally conductive filler, based on the total weight of the composition.
[0033] The inventors have unexpectedly found that a thermally conductive phase change material with excellent overall performance can be obtained by using the base polymer defined in the present invention in a thermally conductive phase change composition. By using the specific base polymer defined in the present invention, it is possible to obtain a thermally conductive phase change material having, in particular, the following excellent properties: good component compatibility, good oxidation resistance, good thermal conductivity and phase transition behavior can be maintained even after aging experiments and long-term thermal shock, no precipitation of components due to long-term thermal shock, non-flammability and easy storage, and particularly suitable for processing by screen printing.
[0034] The base polymer of the present invention can be prepared by methods known to those skilled in the art. For example, the base polymer can be prepared by reacting a polyether, a polysiloxane, and an antioxidant in the presence of a catalyst.
[0035] In particular, taking the case where the polyether is an allyl polyoxyethylene ether, the polysiloxane is a hydrogen-containing silicone oil, and the antioxidant is methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate as an example, the base polymer is prepared by a method including the following steps: 1) Add allyl polyoxyethylene ether to the reaction vessel, raise the temperature to 60-90℃, fill with nitrogen, stir mechanically, and add catalyst A to the reaction vessel after the temperature becomes constant; 2) adding hydrogen-containing silicone oil to the reaction vessel; 3) reacting allyl polyoxyethylene ether with hydrogen-containing silicone oil, and after completion of the reaction, distilling under reduced pressure to obtain polyether silicone oil; 4) Add a certain amount of polyether silicone oil and β-(3,5-di-tert-butyl-4-hydroxyphenyl)methyl propionate into a reaction vessel, fill with nitrogen, add catalyst B, mix uniformly, and react under reflux; preferably, the reflux reaction temperature is 120-160°C, and the reaction time is 6-9 hours. 5) Filter the solution obtained in step 4) through a filter and distill the filtered clear solution under reduced pressure at a temperature of 80-120°C for 2-4 hours to obtain the final product.
[0036] Catalyst A is preferably a platinum catalyst, and more preferably any one selected from chloroplatinic acid, Spear's catalyst, Karstedt's catalyst, and solid-phase platinum catalyst.
[0037] Catalyst B is preferably a solid catalyst, and more preferably an acidic solid catalyst such as an acidic resin or acidic clay.
[0038] The reaction vessel is preferably a four-neck flask.
[0039] In step 2), the hydrogen-containing silicone oil can be pumped into the reaction vessel using a peristaltic pump; and / or the addition rate of the hydrogen-containing silicone oil can be 0.5-20 ml / min.
[0040] In step 3), the reaction of the allyl polyoxyethylene ether with the hydrogen-containing silicone oil can be carried out at a temperature of 80-100°C for 3-5 hours; and / or the distillation under reduced pressure can be carried out at a temperature of 90-110°C for 2-4 hours.
[0041] Hydrogen-containing silicone oils are well known to those skilled in the art. Their use and selection are also within the scope of the ability of those skilled in the art. In general, hydrogen-containing silicone oil refers to polysiloxanes, preferably linear polysiloxanes, having a certain number of Si-H bonds, which are usually liquid at room temperature. The hydrogen-containing silicone oil is preferably a terminal hydrogen-containing silicone oil. Advantageously, the hydrogen-containing silicone oil used according to the present invention has a viscosity of 3-400 mm at 25°C when measured at 25°C using a capillary viscometer according to the national standard GB / T10247-2008 viscosity measurement method standard. 2 / s, preferably 6 to 150 mm 2 / s, more preferably 7 to 50 mm 2 / s. Also advantageously, the Si-H content of the hydrogen-containing silicone oil used according to the present invention is preferably 0.4% to 8.7%, more preferably 0.7% to 7.5%, and most preferably 1.6% to 6.0%, calculated based on the mass ratio of SiH.
[0042] Preferably, the molar ratio of allyl polyoxyethylene ether to hydrogen-containing silicone oil is 0.8:1 to 1.2:1.
[0043] Preferably, the molar ratio of polyether silicone oil to methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is from 0.8:1 to 1.6:1.
[0044] The mass of catalyst A is preferably 0.5 to 20 ppm based on the total mass of allyl polyoxyethylene ether and hydrogen-containing silicone oil; and / or the mass of catalyst B is 1% by mass to 5% by mass based on the total mass of polyether silicone oil and methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.
[0045] The composition according to the present invention can be applied by utilizing screen printing technology. For example, the composition of the present invention can be coated on the interface of the heat sink using screen printing technology. Screen printing technology is an application technology that can precisely control the coating thickness, adjust the coating thickness by controlling the thickness and mesh (pore size) of the screen, and filter out some of the large particle impurities. Coating using screen printing technology is beneficial to further reduce the thermal resistance between the heat sink and the heating element, and at the same time, saves materials, effectively prevents the overflow of the coated excess material, avoids the contamination of other components, and eliminates potential hidden dangers. The composition of the present invention is suitable for coating using screen printing technology because it has the following excellent properties: 1) good flowability during processing; 2) the particle size of the filler contained therein is much smaller than the pore size of the screen; 3) no cross-linking due to chemical reaction or crystallization of certain components occurs during the process of screen printing.
[0046] As an example, the composition according to the invention may be used by a method comprising the following steps: 1) The thermally conductive phase change composition of the present invention is filled into a screen printing device equipped with heating and constant temperature functions; 2) Heat to 35-60℃ and keep at a constant temperature; 3) Using a screen printing device, coat the thermally conductive phase change composition onto electronic components that require heat dissipation, such as CPU, GPU, etc.; 4) The coated electronic components are transported to the cooling zone by a belt conveyor, rapidly cooled to below 5℃, and packaged together with the electronic components after the thermally conductive phase change material is solidified; 5) Alternatively, after completing step 3), the electronic components coated with the thermally conductive phase change material are directly assembled with heat dissipation fins to be packaged as a whole.
[0047] According to another aspect, the present invention relates to the use of a base polymer as defined herein as a thermally conductive phase change material. Preferably, the base polymer is used in a thermally conductive phase change composition.
[0048] According to yet another aspect, the present invention relates to a thermally conductive phase change product obtained by using the thermally conductive phase change composition of the present invention. The thermally conductive phase change product according to the present invention can be prepared by mixing various components in the thermally conductive phase change composition. Specifically, the various components are added to a high-speed stirring tank, heated to 60-90°C, stirred at a speed of 300-500 r / m under a negative pressure of -0.085 MPa for 30-60 minutes, and then discharged in a molten state to obtain a thermally conductive phase change product.
[0049] The thermally conductive phase change product may be in an easy to store form, for example, in the form of sheets, strips, rings, spheres, or cubes, depending on the particular application.
[0050] Preferably, the thermally conductive phase change product can be used as a heat dissipation element, for example, the heat dissipation element can be disposed between a heat-generating electronic component and a heat dissipation sheet component.
[0051] Preferably, the thermally conductive phase change product can be applied or placed between the heat generating electronic component and the heat dissipating sheet component by heated screen printing. [Brief description of the drawings]
[0052] [Figure 1] FIG. 1 shows the DSC analysis of the thermally conductive phase change material according to Example 1 of the present invention, whose endothermic-exothermic behavior was studied using a heating and cooling rate of 5° C. / min. [Diagram 2] FIG. 2 shows the DSC analysis of the thermally conductive phase change material according to Example 1 of the present invention, whose endothermic-exothermic behavior was studied using a heating and cooling rate of 2° C. / min. [Diagram 3] FIG. 3 shows the endothermic-exothermic behavior of the thermally conductive phase change material according to Example 1 of the present invention during 30 cycles, studied using heating and cooling rates of 10° C. / min. [Figure 4] FIG. 4 shows the IR spectrum of the polyether silicone oil obtained in the production process (3) of the base polymer A. [Diagram 5]FIG. 5 shows the IR spectrum of the obtained base polymer A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0053] The present invention is further described below in conjunction with specific examples.
[0054] The raw materials used in the examples are as follows: (1) Allyl polyoxyethylene ether: the number of repeating units in the chain is 18 to 42; (2) Hydrogen-containing silicone oil: terminal hydrogen-containing silicone oil, the number of repeating units in the chain is 10-80, and the viscosity is 6-150 mm when measured at 25°C using a capillary viscometer according to the national standard GB / T10247-2008 viscosity measurement method. 2 / s;Grade 620V3-150, manufactured by Jiangxi Bluestar Xinghuo Silicones Co., Ltd.; (3) Methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate: analytical purity; (4) Catalyst A: Karstedt catalyst, platinum content 3000 ppm; (5) Catalyst B: acidic resin, particle size 0.335-1.25 mm, hydrogen production rate ≧99.9%, large pore strong acid cation exchange resin with styrene-divinylbenzene copolymer skeleton; (6) Thermally conductive filler: industrial grade, with characteristics as specified in the examples; (7) Methyl silicone oil: grade 47V100-1000, manufactured by Jiangxi Bluestar Xinghuo Silicones Co., Ltd.; (8) Antioxidant 1706: Made by BASF.
[0055] 1. Preparation of the base polymer: Step 1): 1 mole of allyl polyoxyethylene ether was added to a four-neck flask, the temperature was raised to 90°C, filled with nitrogen, and mechanically stirred. After the temperature became constant, a total of 10 ppm of catalyst A was added to the four-neck flask; the chain bond number of the allyl polyoxyethylene ether used determines the value of n1 in the reaction product, and these two values are equal, and the corresponding relationship is shown in Table 1 below; Step 2): 1 mole of hydrogen-containing silicone oil was pumped into the four-neck flask at a rate of 1 ml / min using a peristaltic pump; the chain bond number of the hydrogen-containing silicone oil used determines the value of n2 in the reaction product, and these two values are equal, and the corresponding relationship is shown in Table 1 below; Step 3): The reaction was carried out at 90°C for 5 hours. Then, vacuum distillation was carried out at 95°C for 4 hours to obtain polyether silicone oil. The IR spectrum of the product contains COC and Si-O-Si absorption peaks, but does not contain C=C and Si-H peaks, which indicates that the allyl polyoxyethylene ether and hydrogen-containing silicone oil have reacted completely. For example, see the IR spectrum of the polyether silicone oil obtained in this step 3) of the process of preparing base polymer A, as shown in Figure 4. Step 4): 1 mole of the polyether silicone oil obtained in step 3) and 2 moles of methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate were added into a four-neck flask, filled with nitrogen, and then catalyst B was added, followed by uniform mixing and reacting under reflux at 140°C for 8 hours; Step 5): The solution obtained in step 4) was filtered through a filter and the filtered clear solution was distilled under reduced pressure at 100° C. for 4 hours to obtain the final product having the following structure: [ka]
[0056] The IR spectrum of the product shows the absorption peaks of C=O and Ar-H, and the product already contains methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate. For example, see the IR spectrum of the base polymer A obtained in step (5), as shown in Figure 5.
[0057] [Table 1] EXAMPLES
[0058] In the following examples, base polymers A to E are used as reaction products.
[0059] 2. Working Example Example 1 The thermally conductive phase change material of this example includes the following components in parts by weight: Base polymer A: 20 parts Hexamethyldisilazane-treated zinc oxide, median particle size D 50 0.5μm: 40 parts Hexamethyldisilazane-treated alumina, median particle size D 50 5μm: 40 parts
[0060] The above components were placed in a high-speed stirring tank, heated to 60° C., stirred at a speed of 500 rpm for 30 minutes under a negative pressure of −0.085 MPa, and discharged in a molten state to obtain the thermally conductive phase change material of Example 1.
[0061] Example 2 The thermally conductive phase change material of this example includes the following components in parts by weight: Base polymer B: 15 parts KH550 treated zinc oxide, median particle size D 50 1μm:65 parts KH550 treated boron nitride, median particle size D 50 20μm:20 parts
[0062] The above components were placed in a high-speed stirring tank, heated to 70° C., stirred at a speed of 400 r / m under a negative pressure of −0.085 MPa for 20 minutes, and discharged in a molten state to obtain the thermally conductive phase change material of Example 2.
[0063] Example 3 The thermally conductive phase change material of this example includes the following components in parts by weight: Base polymer C: 10 parts Stearic acid treated alumina, median particle size D 50 1μm: 40 parts Stearic acid treated alumina, median particle size D 50 10μm:50 parts
[0064] The above components were placed in a high-speed stirring tank, heated to 70° C., stirred at a speed of 500 rpm for 30 minutes under a negative pressure of −0.085 MPa, and discharged in a molten state to obtain the thermally conductive phase change material of Example 3.
[0065] Example 4 The thermally conductive phase change material of this example includes the following components in parts by weight: Base polymer D: 20 parts Dodecyltrimethoxysilane-treated cerium oxide, median particle size D 50 1μm: 40 parts Dodecyltrimethoxysilane-treated cerium oxide, median particle size D 50 8μm: 40 parts
[0066] The above components were placed in a high-speed stirring tank, heated to 70° C., stirred at a speed of 500 rpm for 30 minutes under a negative pressure of −0.085 MPa, and discharged in a molten state to obtain the thermally conductive phase change material of Example 4.
[0067] Example 5 The thermally conductive phase change material of this example includes the following components in parts by weight: Base polymer E: 8 parts Hexamethyldisilazane-treated zinc oxide, median particle size D 50 0.5μm: 35 parts Median particle size D 50Copper powder with a diameter of 2 μm: 30 parts Median particle size D 50 Copper powder with a particle size of 15 μm: 27 parts.
[0068] The above components were placed in a high-speed stirring tank, heated to 70° C., stirred at a speed of 400 rpm for 40 minutes under a negative pressure of −0.085 MPa, and discharged in a molten state to obtain the thermally conductive phase change material of Example 5.
[0069] Comparative Example 1 The base polymer in Example 1 was replaced with the same part by weight of methyl silicone oil having a viscosity of 350 mPa·s, and the other components were the same as in Example 1, and the manufacturing process was also the same.
[0070] Comparative Example 2 The base polymer in Example 2 was replaced with the same part by weight of methyl silicone oil having a viscosity of 500 mPa·s, and the other components were the same as in Example 2, and the manufacturing process was also the same.
[0071] Comparative Example 3 The base polymer of Example 3 was replaced with the same part by weight of methyl silicone oil having a viscosity of 1000 mPa·s, and the remaining components were the same as in Example 3, and the manufacturing process was also the same.
[0072] Comparative Example 4 Instead of the base polymer A in Example 1, a polyether silicone oil was used, which has the following structure, obtained from steps 1) to 3) of the base polymer preparation process: [ka] In the formula, n1=18, n2=13, and R1 is -H. On the other hand, the remaining components were not changed from those in Example 2, and the manufacturing process was also the same.
[0073] Comparative Example 5 Instead of the base polymer B in Example 2, a polyether silicone oil was used, which has the following structure, obtained from steps 1) to 3) of the base polymer preparation process: [ka] In the formula, n1=24, n2=80, and R1 is -H. On the other hand, the remaining components were not changed from those in Example 2, and the manufacturing process was also the same.
[0074] Comparative Example 6 In Comparative Example 5, 1 part of antioxidant 1076 was added, and the other components were not changed, and the manufacturing process was also the same.
[0075] The material of Example 1 was subjected to DSC analysis. Its endothermic-exothermic behavior was studied using heating and cooling rates of 5° C. / min and 2° C. / min, respectively (FIGS. 1 and 2), and its endothermic-exothermic behavior over 30 cycles was studied using heating and cooling rates of 10° C. / min (FIG. 3).
[0076] The properties of the materials in the above examples and comparative examples (Table 1) were tested according to the following standards. 1) Thermal conductivity was measured using a hot disk apparatus, and sample preparation and testing were performed according to ISO22007 standard; 2) The melting endothermic peak temperature was measured by DSC at a heating rate of 5°C / min and was determined as the endothermic peak apex; 3) Thermal conductivity and melting endothermic peak temperature after aging at 85℃ and 85%RH (Double 85) for 1000 hours; 4) Thermal conductivity and melting endothermic peak temperature after 100 repeated thermal shocks from -40℃ to 125℃; 5) The sample was clamped between two anodized alumina blocks measuring 50mm x 50mm x 2mm, and subjected to 100 cycles of thermal shock from -40℃ to 125℃, after which the presence or absence of precipitation of components was observed; 6) Using a screen printing device, the thermally conductive phase change materials of the above examples and comparative examples were each applied to an anodic alumina block of 50 mm x 50 mm x 2 mm, and the area percentage of the anodic alumina block that could be coated with the thermally conductive phase change material at different processing temperatures was compared.
[0077] [Table 2]
[0078] [Table 3]
[0079] As can be seen from FIG. 1, the sample of Example 1 has a significant endothermic behavior from 20°C to 37°C at a heating rate of 5°C, at which the polymer in the system transitions from solid phase to liquid phase, and the endothermic peak value is about 32°C; in the cooling process at the same rate, the sample shows a significant exothermic behavior from 14°C to 4°C, at which the polymer in the system transitions from liquid phase to solid phase, and the exothermic peak value is about 9°C.
[0080] When applying the product of the present invention, it is only necessary to raise the temperature of the material above the melting temperature range to achieve screen printing; after printing is completed, the cooling temperature only needs to be lower than the liquid-solid transition temperature to resolidify the material, which facilitates packaging and transportation. The scope of protection of the present invention for the screen printing application of the product includes, but is not limited to, the temperature ranges included in the examples.
[0081] From FIG. 2, it can be seen that the phase transition temperature of the system changes with the change in heating and cooling rate.
[0082] From FIG. 3, it can be seen that the phase transition behavior of the sample of Example 1 of the present invention is almost consistent over 30 cycles when tested at the same heating and cooling rates using a DSC instrument, indicating that the system has good stability.
[0083] Comparing the test results (Table 2), it can be seen that the samples of Examples 1 to 5 have good thermal conductivity and phase transition behavior after high temperature and high humidity aging and thermal shock tests. In addition, even after clamping the alumina block and performing thermal shock tests, no separation of components occurred, showing good use performance. Since the polymer structures of Examples 1 to 5 are different, the melting endothermic peaks also change accordingly, indicating that the phase transition temperature of the system can be adjusted by changing the polymer structure to meet different needs. The present invention includes, but is not limited to, the phase transition temperatures included in the examples.
[0084] Comparative Examples 1 to 3 do not show phase transition behavior because they do not use a base polymer with phase transition ability. When an alumina block is clamped and a thermal shock test is performed, the system thickens and dries due to partial precipitation of the silicone oil, which affects the performance in use.
[0085] In Comparative Examples 4 and 5, under the same conditions as in the Examples of the present invention, since the base polymer does not have an antioxidant group, the material is easily oxidized in environmental tests such as high temperature and humidity and thermal shock, hardens, loses its phase transition behavior, and cannot be used normally.
[0086] In Comparative Example 6, the addition of the antioxidant component improved the resistance to high temperature and high humidity compared to Comparative Examples 4 and 5, but the sample hardened locally when subjected to multiple thermal shocks, and the hardened parts lost their phase transition behavior.
[0087] The comparison results of processing performance (Table 3) show that the samples of Examples 1 to 5 can perform good screen printing when heated to the phase transition temperature or higher.
[0088] The samples of Comparative Examples 1 and 2 have low viscosity, so they can be used for screen printing. However, since they do not have phase transition behavior, they do not solidify even if the temperature is lowered after screen printing, and there is a risk that they may be partially wiped off if they come into contact during packaging or transportation. However, the samples of Examples 1 to 5 cannot be wiped off even if they are lightly touched after solidification.
[0089] The sample of Comparative Example 3 had too high a viscosity, so that the screen printing effect was not sufficient, and no significant improvement was observed even when the processing temperature was increased.
[0090] The samples of Comparative Examples 4, 5, and 6 differ only in that the base polymer does not contain an antioxidant group compared to Examples 1 and 2, and have almost no effect on other properties and no obvious effect on the screen printing effect.
Claims
1. A thermally conductive phase change composition comprising a multifunctional modified polysiloxane as a base polymer and a thermally conductive filler, the multifunctional modified polysiloxane having the following structure: 【Chemistry 1】 (In the formula, n 1 is an integer from 10 to 100, and n 2 is an integer from 6 to 120.) 1. A thermally conductive phase change composition comprising:
2. n 1 is an integer from 12 to 60, and n 2 2. The thermally conductive phase-change composition of claim 1, wherein is an integer from 6 to 100.
3. 3. The thermally conductive phase change composition of claim 1 or 2, wherein the thermally conductive filler is selected from aluminum hydroxide, alumina, zinc oxide, cerium oxide, aluminum nitride, boron nitride, silicon nitride, silicon carbide, graphene, carbon nanotubes, quartz powder, aluminum powder, copper powder, silver powder, and mixtures thereof.
4. 4. The thermally conductive phase change composition of claim 1, wherein the thermally conductive filler is surface-treated with a treating agent, the treating agent being selected from stearic acid, zinc stearate, calcium stearate, 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, N-[3-(trimethoxysilyl)propyl]ethylenediamine, methyl 3-(2-aminoethylamino)propyldimethoxysilane, 3-(triethoxysilyl)propyl methacrylate, diaminosilane-containing silane oligomers, hexamethyldisilazane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, vinyltrimethoxysilane, and mixtures thereof.
5. 5. The thermally conductive phase change composition of claim 1, wherein the thermally conductive phase change composition comprises 5-30 wt. % of the multifunctional modified polysiloxane, based on the total weight of the composition, and / or the thermally conductive phase change composition comprises 70-95 wt. % of the thermally conductive filler, based on the total weight of the composition.
6. A thermally conductive phase change product obtained using the thermally conductive phase change composition according to any one of claims 1 to 5, the thermally conductive phase change product being in the shape of a sheet, a strip, a ring, a sphere or a cube.
7. 7. The thermally conductive phase change product of claim 6, which is a heat dissipation element.
8. Use of the base polymer according to any one of claims 1 to 5 as a thermally conductive phase change material.
Citation Information
Patent Citations
Organic silicon resin, preparation method and application thereof
CN111647161A
Thermoconductive silicone composition, thermoconductive material and thermoconductive silicone grease
JP1998110179A
Heat-conductive grease composition
JP2011057879A
